Devir-flor : a mulher buscando superar a depressão - Poton, Wanêssa Lacerda (2010)
An experimentation deeply experienced with a group of women diagnosed as depressive and followed by Mental Health Program from a Health Care Unit in the City of Vila Velha-ES. There were four qualitative workshops, in which the mechanism used were children ballads, drawing with modeling clay, dramatization and dance; this work had approaches which potencialized the process of self-analysis and self management of these women: the Schizoanalisys – as a conception willing-ethical-aesthetic-revolutionary of the life and the world -, and the Schizodrama – as a space of production of the revolutionary and the new -, they had given the tone of the events. Trying to turn aside the conventional group work, marked by the repetition, klínicas proposal is to offer the possibility of proliferation of multiplicities. During the workshops a number of sad events of their lives, part of a perpetual gift, had been revisited; but, since nobody can be depressive twenty four hours a day, happy events also happened – original amorphous jokes -, which allowed these women, in a joy explosion, like a metamorphosis into flowers. These women (and one man), with singular histories and peculiar ways of living, had lived productive-willing-revolutionary processes of the life and the world, with the production of the new.